การพัฒนาเครื่องมือประเมินปัจจัยที่ส่งผลต่อความสำนึกรับผิดชอบร่วมกันของครู ในผลการเรียนรู้ของนักเรียน - คุณวัฒน์บัณฑิต, สุมิตรา; ภิรมย์สมบัติ, ชยุตม์ (An Online Journal of Education, 2015)
บทความนี้เป็นส่วนหนึ่งของงานวิจัยเรื่องปัจจัยที่ส่งผลต่อความสำนึกรับผิดชอบร่วมกันของครูในผลการเรียนรู้ของนักเรียน มีวัตถุประสงค์เพื่อพัฒนาเครื่องมือในประเมินปัจจัยที่ส่งผลต่อความสำนึกรับผิดชอบร่วมกันของครูในผลการเรียนรู้ของนักเรียน เครื่องมือวิจัยคือ แบบสอบถาม มีลักษณะเป็นมาตรประมาณค่า (rating scale) 5 ระดับ ตัวอย่างวิจัย คือ ครู-อาจารย์ ที่ปฏิบัติหน้าที่สอนในโรงเรียนสาธิตของมหาวิทยาลัยรัฐสังกัดสำนักงานคณะกรรมการการอุดมศึกษาในกรุงเทพมหานคร จำนวน 40 คน ผลการตรวจสอบคุณภาพเครื่องมือพบว่า การตรวจสอบคุณภาพแบบสอบถามเกี่ยวกับการปฏิบัติหน้าที่ของอาจารย์โรงเรียนสาธิต จำนวน 44 ข้อ มีค่าความตรงเชิงเนื้อหาอยู่ระหว่าง .80 ถึง 1.00 มีค่าสัมประสิทธิ์ความเที่ยงแต่ละตัวแปรอยู่ระหว่าง .723 ถึง .903 และมีค่าสัมประสิทธิ์ความเที่ยงทั้งฉบับเท่ากับ .955 ผลการตรวจสอบความตรงเชิงโครงสร้างด้วยวิธีการวิเคราะห์องค์ประกอบเชิงยืนยัน (confirmatory factor analysis) ขององค์ประกอบความสำนึกรับผิดชอบร่วมกันของครูทั้ง 4 องค์ประกอบ ได้แก่ การจัดกิจกรรมการเรียนการสอนของครูร่วมกันที่มีต่อนักเรียน การพัฒนาผลสัมฤทธิ์ทางการเรียนของนักเรียน การสร้างแรงจูงใจให้กับนักเรียน และการสร้างปฏิสัมพันธ์ของครูกับนักเรียน พบว่า โมเดลความสำนึกรับผิดชอบร่วมกันมีความสอดคล้องกับข้อมูลเชิงประจักษ์ โดยพิจารณาจากค่าไคสแควร์ มีค่าเท่ากับ 0.03 ซึ่งมีความน่าจะเป็นเท่ากับ 0.866 ที่องศาอิสระเท่ากับ 1 (chi-square =0.03, df=1, p= 0.866, GFI=1, AGFI=0.996, RMR=0.0008, RMSEA=0.000) This paper is a part of research focusing on factors affecting teachers’ sense of shared responsibility in students’ learning outcomes. The purpose of this paper is to report the development of an instrument for measuring teachers’ sense of shared responsibility in students’ learning outcomes. To examine the instrument’s quality, data from 40 teachers of Chulalongkorn University Demonstration School were collected via a questionnaire survey. The data analysis consisted of reliability analyses using SPSS version 22, and confirmatory factor analyses using LISREL version 9.1. The findings were as follows: The instrument developed for measuring the factors affecting teachers’ sense of shared responsibility in students’ learning outcomes is a 44-item 5-point Likert scale. The content validity was checked by IOC of each item ranged from .08 to 1.00. The reliabilities of items for each factor range from .723 to .903 and the overall reliability is .955, showing that the developed instrument has a high level of internal consistency. The component of teachers’ sense of shared responsibility consists of 4 factors: teachers’ sense of shared responsibility in learning activities, students’ achievement, students’ motivation and teacher-student interaction. The results of construct validity reported the model of teachers’sense of shared responsibility fitted to the empirical data. (chi-square = 0.03, df=1, p-value=.866, GFI=1, AGFI=.996, RMR=0.0008, RMSEA=0.000)